EARTH OBSERVATION FOR LAND COVER AND HUMAN-ENVIRONMENT INTERACTIONS - Z. Zhang; Y. Song; P. Luo; P. Wu (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2022)
Human-environment interactions (HEI) are dynamic processes involving a wide range of research areas. The complicated interaction processes, with land cover change as an intermediate process, have been investigated for decades. Urban construction, as a type of human activity, is an important part of the HEI. Earth observation (EO) techniques offer disclosure of physical and chemical properties, from spectral information to chemical compositions, on the earth surface. These advanced technologies have been applied from space to the ground, covering smart urban construction, land cover monitoring and other topics under the scope of HEI. The aim of this paper is to review the significance and contribution of earth observation in HEI research. This paper summarised the utility of four types of earth observation regarding topics of urban construction and land cover monitoring under the scope of HEI. Furthermore, this paper reviewed four advanced techniques in earth observation, including Radar, unmanned aerial vehicles (UAVs), machine learning algorithms and advanced computing platforms like Google Earth Engine (GEE), which can lead to future development in smart urban construction and smart city design.